Associations between personality and uptake of tobacco smoking: Do they differ across adolescence?. (16th August 2019) - Kelly, Erin V.; Grummitt, Lucinda; Teesson, Maree; Newton, Nicola C.
Abstract: Introduction and Aims: Tobacco use is one of the leading causes of death globally, yet it is entirely preventable. Tobacco smoking typically begins in adolescence, and thus efforts to intervene early are vital. Personality has been identified as a risk factor for smoking in adolescence. The current study aimed to examine whether associations between personality traits (impulsivity, sensation‐seeking, anxiety sensitivity and hopelessness) and new onset tobacco smoking differ across adolescence. Design and Methods: At baseline, 527 secondary‐school students (mean age 13 years) completed a validated personality questionnaire and were surveyed on recent tobacco smoking. Participants were followed‐up at 12‐, 24‐ and 36‐months. Logistic regression was conducted to examine prospective associations between the four personality types and tobacco smoking at each follow‐up. Results: Results revealed age‐related differences in the associations between personality and smoking in adolescence. Baseline sensation‐seeking was significantly associated with new onset tobacco smoking at age 14; baseline impulsivity was significantly associated with new onset tobacco smoking at age 15; and baseline hopelessness was significantly associated with new onset tobacco smoking at age 16. Discussion and Conclusions: This study extends knowledge by demonstrating age‐specific effects on the association between personality and smoking. This has important implications for prevention and could inform the development of tailored smoking interventions to be delivered at different ages. Future research will examine personality‐targeted intervention in reducing tobacco smoking in Australian adolescents across different ages.